Degradation of the UV-filter benzophenone-3 in aqueous solution using persulfate activated by heat, metal ions and light. (April 2018) - Pan, Xiaoxue; Yan, Liqing; Qu, Ruijuan; Wang, Zunyao
Abstract: The goals of this study were to bring forward new data and insights into the effect of activation methods, operational variables and reaction pathways during sulfate radicals-based oxidation of benzophenone-3 (BP-3) in aqueous solution. Heat, transition metal ions (Fe 2+, Cu 2+, Co 2+ ), UV and visible light irradiation were used to activate persulfate (PS) to degrade BP-3. The results showed that these three activation methods can remarkably enhance BP-3 removal efficiency. Under the conditions of [BP-3]0 : [PS]0 = 1: 500, pH = 7.0, and 40 °C, complete removal of BP-3 (1.31 μM) was observed in 3 h. In the pH range of 3.0–9.0, the degradation of BP-3 decreased with increasing pH. Increasing the PS dosage accelerated the reaction, while the presence of humic acid (HA) significantly inhibited the efficiency of BP-3 removal. Based on electron paramagnetic resonance (EPR) and radical quenching studies, sulfate and hydroxyl radicals contributed to the oxidation process. According to the evolution of BP-3 and its 7 by-products, as well as frontier electron densities (FED) calculation, two routes were proposed involving hydroxylation, demethylation and direct oxidation. On the whole, this work is a unique contribution to the systematic elucidation of BP-3 removal by PS. Graphical abstract: Image 1 Highlights: Heat, light and metal ions are effective to activate PS for BP-3 degradation. Kinetics and mechanisms of BP-3 degradation by PS were studied. and OH both were the responsible radicals for BP-3 decomposition. 7 transformation products were identified by LC-TOF-MS. Hydroxylation, demethylation and direct oxidation were observed.